Interpretação dos interesses adequação e utilidade das ações coletivas trabalhistas que tutelam direitos individuais homogêneos sob a ótica do acesso à Justiça - Silva, Wallace Antonio Dias (2020)
Through descriptive, theoretical and bibliographical examination it’s studied the general and labor collective actions’s microsystem, especially the collective labor actions that protect homogeneous individual interests and their adequacy and usefulness regarding the legitimacy of acting of the Trade Unions in defense of these in court. The research has, by assumption, a methodological analysis with the presentation of the theoretical assumptions used. Its grounding is essentially theoretical by the study of Brazilian and foreign doctrines and laws and the jurisprudential appreciation that accompanies every debate in order to present their senses and practical effects in an intersection between logic and praxis. The proposal is to demonstrate, based on philosophical (legal culturalism and dialectical complementarity), theoretician of law (critical positivism) and sociological (mass society and post-work) assumptions and from studies on the theme “access to Justice” that the Brazilian Labor Judiciary does not guarantee true access to fair jurisdiction for the parties involved in the capital-labor relationship and, as a consequence, deepen into the general and labor collective actions’s microsystem to find possible solutions and alternatives to the obstacle encountered. In particular, the active legitimation of Trade Unions and their interests is considered as appropriate and useful for bringing collective labor lawsuits to protect homogeneous individual interests. A practical, legal and social analysis of the characteristics of each of the concepts is performed, exposing their definitions and finding their specificities. Finally, the relationship between all the institutes is studied in greater depth and practical examples of the thesis presented are presented